2018
DOI: 10.1371/journal.pone.0201982
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of unique enzymes in Xanthomonas euvesicatoria related to degradation of arabinofurano-oligosaccharides on hydroxyproline-rich glycoproteins

Abstract: In this study, we clarified the functions of three uncharacterized enzymes, XCV2724, XCV2728, and XCV2729, in Xanthomonas euvesicatoria, the causal agent of bacterial spot of tomato and pepper. The genes corresponding to the three enzymes are homologs of hypBA1, hypBA2, and hypAA from Bifidobacterium longum and are unique to Xanthomonas spp. among plant pathogenic bacteria. Functional characterization of the recombinant enzymes expressed using microbial systems revealed that they degrade the arabinofurano-olig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 40 publications
0
24
0
Order By: Relevance
“…Bifidobacteria are representative species of gut microbes that are beneficial to human health while Xanthomonas species contain pathogens that cause bacterial spots on a wide variety of plant species. The genes for β-L-arabinooligosaccharide-degradation enzymes in X. euvesicatoria (xehypBA1-BA2-AA) are not involved in either pathogenicity or non-host resistance reactions [42]. However, the distribution of GH121 genes suggests that bifidobacteria and Xanthomonas species possibly benefit from the disaccharide-releasing enzyme and the disaccharide-specific importer system on their biological niches in order to live on special types of plant glycans, such as Ara 3 -Hyp β-L-arabinooligosaccharides on HRGPs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bifidobacteria are representative species of gut microbes that are beneficial to human health while Xanthomonas species contain pathogens that cause bacterial spots on a wide variety of plant species. The genes for β-L-arabinooligosaccharide-degradation enzymes in X. euvesicatoria (xehypBA1-BA2-AA) are not involved in either pathogenicity or non-host resistance reactions [42]. However, the distribution of GH121 genes suggests that bifidobacteria and Xanthomonas species possibly benefit from the disaccharide-releasing enzyme and the disaccharide-specific importer system on their biological niches in order to live on special types of plant glycans, such as Ara 3 -Hyp β-L-arabinooligosaccharides on HRGPs.…”
Section: Discussionmentioning
confidence: 99%
“…186 sequences from Xanthomonas species formed a very large group with little or no sequence diversity, 175 of them being in a zero branch between them. A HypBA2 homolog from Xanthomonas euvesicatoria (XeHypBA2) [42] was also included in this cluster. The full amino acid sequence alignment revealed that the amino acid residues at the Ca2 site are essentially conserved in GH121, whereas those at Ca1 and Ca3 are not conserved (S3 Fig) . Sequence logos around the three acidic residues (E383, D515, and E713, Fig 4B) illustrated that all of them are completely conserved in GH121, and nearby sequences are also highly conserved.…”
Section: Sequence Analysis Of Gh121mentioning
confidence: 99%
“…Several GHs from different bacterial sources have been described that hydrolyze specific linkages within O-glycans of EXTs (Table 2). The GH127 enzyme from Xanthomonas euvesicatoria XeHypBA1 was described as a β-L-(1 → 2)arabinofuranosidase (Nakamura et al, 2018) while two GH121 members, one from Bifidobacterium bifidum HypBA2 and XeHypBA2, were shown to hydrolyze the β-L-Araf -(2 → 1) linkages (Fujita et al, 2011(Fujita et al, , 2014Nakamura et al, 2018). (Nakamura et al, 2018) (Table 2 and Figure 2).…”
Section: Extensins-glycans Gts and Ghsmentioning
confidence: 99%
“…Our preliminary study indicated that transcription levels of the b-arabinooligosaccharide utilization genes (BLLJ_0208, BLLJ_0211, BLLJ_0212, and BLLJ_0213) were upregulated when B. longum JCM 1217 was grown with b-Ara 2 as the sole carbon source, but not with L-arabinose (data not shown). The xehypBA2-AA operon in X. euvesicatoria (plant pathogen) notably contains homologous genes of HypAA, HypBA2, and HypBA1 but does not have transporter genes [24]. The uptake system specific to b-Ara 2 may be specific to and required by these bifidobacterial species to effectively utilize carbon sources from plants in competition with other bacteria.…”
Section: Biological Implicationsmentioning
confidence: 99%
“…We previously reported structural and functional characterizations of HypBA1 [22,23] and a similar enzymatic degradation system from the plant pathogenic bacterium Xanthomonas euvesicatoria [24]. Here, we aimed to determine the three-dimensional structure and molecular and mechanistic functions of the SBP (BLLJ_0208) using X-ray crystallography, thermal shift assays, isothermal titration calorimetry (ITC), and molecular dynamics (MD) simulation.…”
Section: Introductionmentioning
confidence: 99%